1992
DOI: 10.1002/bbpc.19920960351
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Photochemical Sources of Atomic Cl in the Troposphere

Abstract: The reaction of N2O5 with wet NaCl aerosol is observed to produce ClNO2 at high yields. The sticking coefficient of N2O5 on NaCl aerosol is determined in a smog chamber (in an inserted teflon bag) at 292 K, and the rate constant for the consecutive chemical reaction leading to formation of ClNO2 is determined at various relative humidities between 71 and 92%. A preliminary evaluation of the experiments yields a sticking coefficient of 0.03(−0,01+0,02), similar to that reported for pure water droplets. At the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 23 publications
1
56
0
1
Order By: Relevance
“…Similar reactions occur also on airborne aerosol surfaces [Behnke and Zetzsch, 1989b]. Further experiments showed that C1NO2 is produced from the reaction of N205 on moist NaC1 aerosol surfaces [Behnke and Zetzsch, 1990;Zetzsch and Behnke, 1992]. Here we describe smog chamber and wetted-wall flow tube experiments, which evaluate the uptake of N20 5 and C1NO2 on water and NaC1 solutions and the C1NO2 yield of the reaction of N20 5 on wet NaC1 aerosol and bulk surfaces.…”
Section: Introductionmentioning
confidence: 92%
“…Similar reactions occur also on airborne aerosol surfaces [Behnke and Zetzsch, 1989b]. Further experiments showed that C1NO2 is produced from the reaction of N205 on moist NaC1 aerosol surfaces [Behnke and Zetzsch, 1990;Zetzsch and Behnke, 1992]. Here we describe smog chamber and wetted-wall flow tube experiments, which evaluate the uptake of N20 5 and C1NO2 on water and NaC1 solutions and the C1NO2 yield of the reaction of N20 5 on wet NaC1 aerosol and bulk surfaces.…”
Section: Introductionmentioning
confidence: 92%
“…A multi-reflection cell (White-cell) coupled with DOAS was used to observe BrO levels directly. The concentrations of OH and Cl radicals were quantified indirectly by monitoring the decay of several hydrocarbons using the radical clock method (Zetzsch and Behnke, 1992). For details on the experimental setup, the analytical methods used and results about RHS release from the salt pan in the absence of SOA, see Buxmann et al (2012).…”
Section: Photochemical Activation Salt-pan Experimentsmentioning
confidence: 99%
“…The formation of even simpler molecules like phosgene, chloroacetone and 1,1-dichloroacetone after interaction of hydrocarbons with halogens released from NaCl aerosol was found by Zetzsch and Behnke (1992) in aerosol smogchamber experiments. A detailed review on these formation pathways is given by Behnke and Zetzsch (2005).…”
Section: Introductionmentioning
confidence: 96%
“…However, if chloride ions are present, there is a competition between the reactions of NO 2 + with water and Cl À , and ClNO 2 is generated: 3,5,8,[10][11][12][13][14][15][16] …”
Section: Introductionmentioning
confidence: 99%
“…In the former case, the HNO 3 product can react further with NaCl [11][12][13][14][15][16][17][18]20,[22][23][24][25][26][27][28][29][30][31][32][33][34] to generate HCl.…”
Section: Introductionmentioning
confidence: 99%